INTERAKSI KOMUNIKASI ORGANISASI - Siregar, adminNina Siti Salmaniah (Universitas Medan Area, 2013)
Organizational communication is a study that will provide benefits not only for anyone who wants to understand better the behavior of the organization, but it also has a pragmatic aspect for people who want to assert performance as a participant or member of an organization . The study of organizational communication can provide a strong foundation for a career in management, human resource development, and corporate communications, as well as other tasks oriented to people within the organization. Communication involves the organization of formal and informal forms of communication, and other forms of interpersonal communication and group communication, and public communication. Approach and understanding of the interaction in organizational communication, we can further improve the performance, achievement, and achieve goals that have been set together.